Fluticasone furoate/vilanterol 200/25 mcg in Asian asthma patients: A randomized trial. Issue 1 (January 2015) - Lin, Jiangtao; Kang, Jian; Lee, Sang Haak; Wang, Changzheng; Zhou, Xiangdong; Crawford, Jodie; Jacques, Loretta; Stone, Sally
Summary Background This study investigated the efficacy and safety of the inhaled corticosteroid (ICS)/long-acting beta2-agonist (LABA) combination fluticasone furoate (FF)/vilanterol (VI) in Asian asthma patients. Methods A 12-week, double-blind, double-dummy, active-comparator, parallel-group, multicenter study. 309 Asian asthma patients (≥12 years, uncontrolled with high-strength ICS or mid-dose ICS/LABA) were randomized (1:1) and included in the intent-to-treat population; 155 received once-daily FF/VI 200/25 mcg and 154 received twice-daily fluticasone propionate (FP) 500 mcg. The primary endpoint was change from baseline in daily evening peak expiratory flow (PEF) averaged over 12 weeks. Secondary endpoints were mean change from baseline in % rescue-free 24-h periods, daily morning PEF, % symptom-free 24-h periods, and overall Asthma Quality of Life Questionnaire score. Safety assessments were performed. Results For change from baseline in daily evening PEF, the adjusted mean treatment difference for FF/VI versus FP of 28.5 L/min (95% confidence interval [CI]: 20.1, 36.9) was clinically and statistically significant (p < 0.001). For change from baseline in % rescue-free 24-h periods, the adjusted mean treatment difference (1.0%; 95% CI: –7.3, 9.2) was not statistically significant (p = 0.821). Statistical significance could not be inferred for the remaining endpoints due to the statistical hierarchy employed. Incidence of on-treatment adverse events was similar with FF/VI (26%; 3% treatment-related; n = 1 serious) and FP (27%; 3% treatment-related; n = 2 serious); none were fatal. No further safety concerns were identified. Conclusions FF/VI improved evening PEF over 12 weeks versus FP in Asian patients, with a similar safety profile. The results are generally consistent with a global study comparing the same treatments.